Defining the Domains of Human Polynucleotide Phosphorylase (hPNPase(OLD-35)) Mediating Cellular Senescence - Sarkar, Devanand (American Society for Microbiology, 2005)
To fully comprehend cellular senescence, identification of relevant genes involved in this process is mandatory. Human polynucleotide phosphorylase (hPNPase(OLD-35)), an evolutionarily conserved 3′, 5′ exoribonuclease mediating mRNA degradation, was first identified as a predominantly mitochondrial protein overexpressed during terminal differentiation and senescence. Overexpression of hPNPase(OLD-35) in human melanoma cells and melanocytes induces distinctive changes associated with senescence, potentially mediated by direct degradation of c-myc mRNA by this enzyme. hPNPase(OLD-35) contains two RNase PH (RPH) domains, one PNPase domain, and two RNA binding domains. Using deletion mutation analysis in combination with biochemical and molecular analyses we now demonstrate that the presence of either one of the two RPH domains conferred similar functional activity as the full-length protein, whereas a deletion mutant containing only the RNA binding domains was devoid of activity. Moreover, either one of the two RPH domains induced the morphological, biochemical, and gene expression changes associated with senescence, including degradation of c-myc mRNA. Subcellular distribution confirmed hPNPase(OLD-35) to be localized both in mitochondria and the cytoplasm. The present study elucidates how a predominantly mitochondrial protein, via its localization in both mitochondria and cytoplasm, is able to target a specific cytoplasmic mRNA, c-myc, for degradation and through this process induce cellular senescence.